Pengaruh Perceived Value dan Trust terhadap Revisit Intention dengan Word of Mouth sebagai Mediasi di Desa Wisata Kampung Tua Bakau Serip Batam - Ratih Anggraini; Dessy Aliandrina; Yellys (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Tourist villages are interesting destinations for many people because tourist villages have their own culture and character. Tourist villages can attract more tourists because they have natural tourism with a diversity of flora and fauna as well as education about tourist villages which have their own characteristics. The Kampung Tua Bakau Serip Tourism Village in Batam is one of the tourist villages that is recognized by the world of tourism and was awarded 3rd place in the ADWI (Anugerah Desa Wisata Indonesia) event. The Kampung Tua Bakau Serip Tourism Village has been developed for the last five years and continues to experience development. The researcher's aim is to analyze the influence of revisit intention in the Kampung Tua Bakau Serip Tourism Village by using perceived value and trust which act as independent variables with word of mouth as mediation. This research analyzes how each variable has an influence, related, and provides a positive impact on each other. This research took samples from people who had visited the Kampung Tua Bakau Serip Tourism Village. The sampling method used non-probability sampling and intentional sampling, and the total sample was 294 respondents. As a survey method, data collection is carried out by distributing questionnaires in the form of Google forms. SEM (Structural Equation Modeling) is a data analysis method using the PLS (Partial Least Squares) technique using computer software, namely SmartPLS. The research results show that perceived value and trust have a positive effect on revisit intention with word of mouth as mediation. Therefore, the Kampung Tua Bakau Serip Tourism Village must be maintained and preserved so that revisit intention can be realized continuously.